DEACON, William Henry D'Ewes Inventory - DEACON, William Henry D'Ewes (ARCA, 2018)
Private papers of W.H.D. Deacon, United Party MPC Albanie [1965-1969], MP Albanie [1969-1977].
COVERAGE 1959-1973; 73 Files; 5,22 Metres.
Keywords: DEACON, William Henry D'Ewes; Inventory; United Party